vFerryman: An Artificial Intelligence-Driven Personalized Companion Providing Calming Visuals and Social Interaction for Emotional Well-Being - Wei-Ji Wang (Engineering Proceedings)
As awareness of mental health issues grows, there is an increasing demand for innovative tools that provide personalized emotional support. By introducing vFerryman, an AI-driven companion system was designed to enhance emotional well-being in this study. The system integrates advanced natural language processing and machine learning technologies into the CrewAI framework. Multiple AI agents were used to deliver personalized, real-time emotional responses. By utilizing large language model operations (LLMOps), vFerryman optimizes the performance of large language models to dynamically adapt to users’ emotional feedback. A key feature of the system is its calming aquarium module, which offers a soothing visual environment to alleviate stress and anxiety. Additionally, vFerryman includes a social interaction platform that fosters emotional connections and shared experiences among users. The effectiveness of vFerryman in improving emotional well-being and facilitating social interaction was evaluated while identifying areas for further technical enhancement and practical applications in emotional support systems.